An experimental study of the tribological characteristics of engine and gear transmission oils - Perić, Sreten (Strojniški vestnik, 2013)
During the past few decades, special attention has been devoted to developing modern instruments and methods of monitoring the tribomechanical characteristics of technical systems. Today, various physical, chemical and tribological methods are used in tribomechanical systems diagnosis. Scientific experience in technical system exploitation and maintenance has shown that the most effective way to predict failure is based on parameters that are reliable indicators of wear. Analysis of oil samples, which contain particles due to the wear process, enables an evaluation of the tribology condition of the system in the early phases of its use. This paper deals with tribological tests that are part of the oil analysis and are used to access the condition of the system. Furthermore, the results of experimental research on the tribological characteristics of the oil sampled from engines and gear transmissions of the vehicles (Mercedes O 345, PUCH 300GD and PINZGAUER 710M) are shown. All of these road vehicle were in regular use by the Serbian armed forces. The performed research has revealed some significant changes in the tribological characteristics of oil for engine and gear transmission lubrication.. These changes directly depend on the condition of the entire engine and transmission elements, i.e. depend on their functional characteristics. The presented method of oil analysis should contribute to an early detection of failures due to friction and wear processes in vehicle engines and reduce the need for preventive maintenance.
Keywords: dinamično modeliranje; dynamic modelling; engine oils; lubricants; maziva; motorna olja; nadzor stanja olja; oil condition monitoring